Colocalization within the Nucleolus of Two Highly Related IFN-Induced Human Nuclear Phosphoproteins with Nucleolin - Welsh, Gavin I.; Kadereit, Suzanne; Coccia, Eliana M.; Hovanessian, Ara G.; Meurs, Eliane F. (My University, 1999)
We have previously reported the identification of two interferon (IFN)-induced cDNAs which code for two proteins, named 41 and 75, which have homology to a number of proteins involved in regulating gene expression. Here we establish that these cDNAs correspond to in vivo synthesized mRNAs. Expression of the 41 and 75 cDNAs, both in vitro and in vivo, generated proteins of 30 and 68 kDa, respectively. In a variety of mammalian cells, 41 and 75 were found to be located in the nucleus, with 41 being localized to the nucleolus, whereas 75, although it is mainly concentrated at the periphery of the nucleolus, is also found throughout the nucleoplasm. Treatment with interferon results in a translocation of 41 to the periphery of the nucleolus and it is in this region that the two proteins colocalize. 41 and 75 were found to colocalize with nucleolin but not with B23 or fibrillarin, three nucleolar proteins involved in ribosome synthesis. This colocalization was not affected by low concentrations of actinomycin D. In view of this and since 41 and 75 have homology to proteins involved in regulating gene expression, we suggest that, in association with nucleolin, they play a role in ribosome biogenesis.
Keywords: 570